MENYIKAPI PERMASALAHAN BELAJAR PESERTA DIDIK DI SEKOLAH : PERAN BIMBINGAN DAN KONSELING - Yulianti, Yulianti; Ramahwati, Novia Tri; Azzahwa, Meyrina; Anjani, Aprilia; Rizky Hudaya, Sania Sauma; Afifah, Fiska Muthia (Dharmas Education Journal (DE_Journal), 2024)
This research aims to explore the role of guidance and counseling in addressing students' learning problems at school. The research method used was a literature review to collect information about the importance of guidance and counseling in the educational context. The results of the analysis show that guidance and counseling have a significant role in helping students overcome various learning problems, such as academic difficulties, low motivation, interpersonal conflicts, and others. A holistic approach based on individual needs can provide effective support for students in developing their potential optimally. The implication of these findings is the need to increase the role and support for counselors and teachers in providing quality guidance and counseling services in the educational environment. It is hoped that this research can contribute to improving the understanding and practice of guidance and counseling in schools to improve learning achievement and student welfare.